Pulmonary laser-assisted metastasectomy is associated with prolonged survival in patients with colorectal cancer - Moneke, Isabelle; Funcke, Friederike; Schmid, Severin; Osei-Agyemang, Thomas; Passlick, Bernward (Journal of Thoracic Disease; Vol 11, No 8 (August 31, 2019): Journal of Thoracic Disease, 2019)
Background: Pulmonary metastases develop in 10–15% of patients with colorectal cancer. Surgical metastasectomy currently provides the only hope for a cure for these patients. The aim of this study was to analyze the expanding role of pulmonary metastasectomy in the context of laser-assisted surgery (LAS) vs. non-laser-assisted surgery (NLAS). Methods: We performed a single-center retrospective analysis of 204 patients who underwent curative pulmonary metastasectomy for colorectal cancer between 01/2005 and 12/2016. The main endpoint was survival. The Kaplan-Meier method was applied for statistical analysis and survival rates were compared with the log rank test. Results: Median follow-up was 53 months. A total of 267 metastases were resected in 154 operations in the NLAS group (median: 1) vs. 438 metastases in 122 operations in the LAS group (median: 5; P